Estudo de prevalência, gravidade e impacto da dor de dente na vida diária de crianças de 8 e 9 anos - Eliane de Paula Reis Barreto (2010)
The aim of the present study was to access the prevalence, severity, impact of dental pain and explanatory factors in schoolchildren of 3 Brazilian cities. The study was a cross-sectional survey conducted in Belo Horizonte, Montes Claros and Curvelo Minas Gerais, Brazil; 1740 children with 8-and-9-year-old were randomly selected from schools, interviewed and clinically examined by a single dentist, after formal authorisation from their parents. Clinical data were assessed using WHO criteria and dental pain, its characteristics and associated factors were recorded using two measures of pain (Child-DPQ and VASOF). The psychometric properties of this instruments, such as validity and reliability, were tested on 174 children from 8 to 9 years old. In relation to Child-DPQ, internal reliability was confirmed by a Cronbach´s alpha coefficient of 0.93. The test-retest reliability revealed excellent reproducibility (ICC = 0.99). The construct validity was satisfactory, demonstrating high significant correlations between global well-being indicator and total scale and subscales scores. Child-DPQ score was able to discriminate between different oral conditions (groups: untreated caries and caries free/treated caries). In regard to VASOF, test-retest reliability revealed satisfactory reproducibility (Weighted Kappa=0.92). Construct validity was satisfactory (p<0.001), showing that VASOF score was able to discriminate different groups of children. In reference to criterion validity, VASOF was compared to a gold standard test (the Wong-Baker Faces Scale), being the correlation found statistically significant (r=0.995/p<0.001). The agreement between researcher and children, relating to gender and race, was also verified by the Kappa test and was satisfactory. After to confirm the appropriate psychometric properties of the data collection instruments, the main study was realized. In the data analysis, multinomial logistic regression was used to assess associated factors to dental pain outcomes. The lifetime and the last month prevalences of toothache were 53.4% (n=929) and 24.4% (n=424), respectively. The main factors associated to prevalence, severity and impact of pain were frequency/reason for going to the dentist and need for dental treatment. Children that going to the dentist for problems, had 5.03 time more chance of report toothache than those that going for prevention; and those with need for dental treatment in three or more teeth, had 4.59 time more chance of report recent toothache than those without need for treatment. Finally, the prevalence, severity and impact of toothache in the population surveyed were higher among children with a greater need for dental treatment and those who do not regularly visit the dentist for prevention.